Pengaruh Penyuluhan IVA Terhadap Tingkat Pengetahuan Wanita Usia Subur - Wa Ode Sri Wati Lestari; Rina Anwar; Lidia Sari (An-Najat, 2023)
Cervical cancer is one of the most common cancers suffered by women. Cervical cancer is cancer of the uterine mouth caused by Human Papiloma Virus (HPV). In Indonesia cervical cancer disease almost 70% of patients with this disease are found in an advanced stage. The number of cervical cancer cases in 2019 in Southeast Sulawesi Province was 128 cases of cervical cancer. The number of WUS who have not participated in the cervical cancer early detection program using the IVA method can be influenced by the lack of information obtained by the community. This study aims to determine the effect of IVA counseling on the level of knowledge of women of childbearing age in Tarafu Village, Batupoaro District, Baubau City. Methods: This study used a pre-experimental type method with The One Group Pre Test-Post Test Design research design. Statistical tests using the Wilcoxon Match Pairs Test. The sampling technique in this study was proposive sampling with the Aikunto formula. Study population: The population in this study were all women of childbearing age in tarafu village which amounted to 180 people. The sample in this study were women of childbearing age who had met the inclusion-exclusion criteria and with the sampling technique with the Arikunto formula n = 25% x N with a total of 45 women of childbearing age. Research Results: The results showed that there was an effect of IVA counseling on the level of knowledge of women of childbearing age in the Betoambari Health Center Working Area, Baubau City 2022, obtained a p-value of 0.000 at a significance degree of 5% (0.000 <0.05). Conclusion: The effect of IVA counseling is effective in increasing the knowledge of women of childbearing age about cervical cancer.